GLOBAL TRENDS AND KNOWLEDGE STRUCTURES IN HALAL TOURISM RESEARCH: INSIGHTS FROM BIBLIOMETRIC ANALYSIS - Julina, Julina; Harahap, Nazruddin Safaat; Zahirah, Qonitah Rifda; Masrizal, Masrizal; Moi, Mohammed Rizki (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
Halal tourism has grown into one of the fastest-growing sectors of the travel industry worldwide, driven by rising demand for Sharia-compliant services. However, practical challenges persist in the industry, such as inconsistent service implementation, uncertainties in operational costs, and ambiguous international standardization. Our research aims to examine halal tourism using published studies from 2020 to 2025 to provide a comprehensive basis for forming a coherent picture of its evolution. Our research examines halal tourism using published studies from 2020 to 2025 to provide a comprehensive overview of its development. In this quantitative study, we utilized a bibliometric analysis approach. We retrieved data from the Scopus database and analyzed them using the Biblioshiny R module to explore publication trends, citation patterns, influential authors, journals, institutions, and country contributions. We also applied a keyword co-occurrence analysis to map the main intellectual and thematic patterns in halal tourism research. The findings demonstrate that Indonesia and Malaysia dominate both publication output and institutional productivity. We found that the Journal of Islamic Marketing is the most frequently cited journal in halal tourism research. The thematic mapping analysis highlights four principal clusters: Muslim consumer behavior and intention; service quality and competitiveness; sustainability and innovation; and governance and certification issues. This study contributes to  our integrative understanding of halal tourism scholarship by providing a comprehensive synthesis of performance indicators and thematic evolution. Our findings reveal emerging directions such as  digital transformation, halal lifestyle, and international collaboration, each of which is expected to guide future research efforts among scholars, practitioners, and policymakers.